(untitled) (Bangladesh Journal of Agricultural Research, 2018)
A field experiment was conducted to study the effect of brackish water on soil physical and chemical conditions and yield of wheat and maize genotypes at the farmers’ field. Two salt tolerant genotypes for each crop were selected from previous hydroponic and lysimeters studies. Wheat-maize cropping system was followed using tubewell brackish water alone and with chemical (gypsum) and organic (FYM) amendments. The results revealed that treatments have significant effect on all growth and yield parameters and followed the trend of T1>T3 >T4 > T2. Highest grain yield of wheat genotypes (SARC-1 & V-8670) was observed in control (4050 & 3800 kg/ha) and lowest was in T2 (2862 & 2200 kg/ha). Similar trend was observed in maize fodder yield that was 9625 & 8875 kg/ha in control and 4350 & 2253 kg/ha in T2 for Sahiwal-02 and Akbar, respectively. Maximum reduction in wheat grain and maize fodder yield observed in T2 (tubewell water alone) where high EC, SAR and RSC water was applied that was 39 & 57% for 1st year (wheat crop) and 89 & 74% for 2nd year (maize crop) respectively. Data revealed that use of gypsum and FYM along with brackish water improved the wheat grain yield and maize fodder as compared to T2. More adverse effect of brackish water was observed in high EC, SAR and RSC treatment (tubewell water alone) as compared to other treatments. Application of amendments (gypsum and FYM) along with brackish tubewell water reduced adverse effect of brackish water. Among genotypes SARC-1 and Sahiwal-2002 performed better in all treatments and textures especially under brackish water treatments. Bangladesh J. Agril. Res. 42(4): 693-705, December 2017